Aymara number system: a revision for its reconstruction - Bizarro, Wilfredo (2020)
In this work, the literature of the Aymara numbering system, its history, coexistence and analysis with respect to different cultures and languages ​​was reviewed, considering their types, principles and characteristics. Based on this, it proceeds to its original reconstruction of the Aymara language numbering system, since there is antecedents and evidence to affirm that it is an oral, regular positional system, in decimal base, with quinary auxiliary, in addition to additive and multiplicative. The primitive root number five was found to be qallqu; original base to which the other numbers follow by addition: maya ‘1’, paya ‘2’, kimsa ‘3’, pusi ‘4’, qallqu ‘5’, maqallqu (maya qallqu ‘1 + 5’), paqallqu (paya qallqu ‘2 + 5’), kimsaqallqu (kimsa qallqu '3 + 5') and pusiqallqu (pusi qallqu ‘4 + 5’), and tunka ‘10’, based on it they form a wonderfully precise order, perfect from the intercultural, linguistic, ethnomathematical and mathematical interpretation.